PERDAGANGAN ORANG (TRAFFICKING IN PERSONS) DITINJAU DARI KUHP DAN HAK ASASI MANUSIA - Fransiska Novita Eleanora (Jurnal ADIL, 2019)
Human trafficking is a type of trade involving public migration and trans-law system, andits existence is illegal for the labors work by force, and its main aim is very much close toslavery. This research applies literature-study method. The findings of this researchsuggest that the number of articles related to the punishments for the involvement in humantrafficking in the Criminal Code (KUHP) is reasonably numerous since such an actsubstantially deprives one’s rights to live, grow, and develop. Human trafficking is alsoclearly against human rights to which a person is inherently entitled. From the humanrights perspective, human trafficking is considered a serious violation which deprives one’srights to live, grow, and develop. The contributing factors of this issue are poverty, pooreducation, poor birth recording system, culture, slavery-like jobs, early marriage, legalpolicy, gender bias, and corruption.